2013
DOI: 10.1126/science.1237874
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Vectors Violate CD8 + T Cell Epitope Recognition Paradigms

Abstract: CD8+ T cell responses focus on a small fraction of pathogen- or vaccine-encoded peptides, and for some pathogens, these restricted recognition hierarchies limit the effectiveness of anti-pathogen immunity. We found that simian immunodeficiency virus (SIV) protein-expressing Rhesus Cytomegalovirus (RhCMV) vectors elicit SIV-specific CD8+ T cells that recognize unusual, diverse and highly promiscuous epitopes, including dominant responses to epitopes restricted by class II major histocompatibility complex (MHC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
516
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(530 citation statements)
references
References 69 publications
12
516
1
1
Order By: Relevance
“…These fit well with the slightly updated version of the definition included in this review. For the rhesus macaque‐based cytomegaloviruses, there are a series of additional modifications regarding immune evasion and, interestingly, cellular targeting which can have quite profound impacts on the specificities observed, some of which are unconventional (eg, HLA‐E restricted) and can have potentially potent antiviral properties 86, 87, 88. Overall—even in settings where more conventional CD8 + T‐cell responses are induced—there is evidence that these responses can provide protection against viruses and cancers 2, 43.…”
Section: Next Stepsmentioning
confidence: 99%
“…These fit well with the slightly updated version of the definition included in this review. For the rhesus macaque‐based cytomegaloviruses, there are a series of additional modifications regarding immune evasion and, interestingly, cellular targeting which can have quite profound impacts on the specificities observed, some of which are unconventional (eg, HLA‐E restricted) and can have potentially potent antiviral properties 86, 87, 88. Overall—even in settings where more conventional CD8 + T‐cell responses are induced—there is evidence that these responses can provide protection against viruses and cancers 2, 43.…”
Section: Next Stepsmentioning
confidence: 99%
“…On the other hand, Hansen et al 90 , 91 reported no protection from virus acquisition but found robust control of viremia in ∼half of the rCMV (SIV Gag) immunized macaques. A fundamental difference between our and the rCMV vaccine is that DNA vaccination induces T cell immunity using canonical MHC molecules, while certain rCMV vectors are able to elicit T cell immunity through the non-canonical MHC-E, 94 , 95 a feature that makes the rCMV vector induced responses unique. In a study designed to mimick elite controllers, Mudd et al 69 reported that vaccination of Mamu B*08 + macaques with recombinant yellow fever 17D (rYF17D)/rAd5 vectors expressing three Mamu B*08 restricted Nef and Vif CD8 epitopes resulted in efficient control of viremia.…”
Section: Discussionmentioning
confidence: 99%
“…A novel CMV vector developed by Louis Picker et al 31, 32, 33. has elicited unusual and protective T‐cell responses in rhesus macaques.…”
Section: T‐cell Vaccine Design Strategiesmentioning
confidence: 99%
“…By using rhesus CMV vectors that lacked particular genes (Rh157.5, Rh157.4, and Rh157.6), a prolific T‐cell response was generated, and a very high density of epitopes was targeted in the SIVmac Gag protein that was included in the vaccine. The responses were restricted either by class II major histocompatibility complex (MHC) molecules,32 or by the conserved, non‐classical, ubiquitously expressed MHC‐E protein 33. The MHC‐E presented epitopes were non‐canonical, meaning that they generally did not contain previously defined MHC‐E anchor motifs 33.…”
Section: T‐cell Vaccine Design Strategiesmentioning
confidence: 99%
See 1 more Smart Citation